Pengaruh Ukuran Perusahaan, Likuiditas, Leverage dan Profitabiltas terhadap Risk Management Disclosure - Widya Puspitaningrum; Taswan Taswan (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
This study aims to examine the effect of company size, liquidity, leverage, and profitability on risk management disclosure. The population of this study are all manufacturing companies listed on the Indonesia Stock Exchange 2016-2018. The sample selection technique was purposive sampling in order to obtain a total number of observations of 144 research samples. Data analysis method used in this study is multiple regression analysis. Partial test shows that company size and liquidity have a positive effect on disclosure risk management, but leverage and profitability do not affect the risk disclosure management.